Super-resolution imaging of C-type lectin spatial rearrangement within the dendritic cell plasma membrane at fungal microbe contact sites - Itano, Michelle S.; Graus, Matthew S.; Pehlke, Carolyn; Wester, Michael J.; Liu, Ping; Lidke, Keith A.; Thompson, Nancy L.; Jacobson, Ken; Neumann, Aaron K. (Frontiers in Physics, 2014)
Dendritic cells express DC-SIGN and CD206, C-type lectins (CTLs) that bind a variety of pathogens and may facilitate pathogen uptake for subsequent antigen presentation. Both proteins form punctate membrane nanodomains ( 80 nm) on naïve cells. We analyzed the spatiotemporal distribution of CTLs following host-fungal particle contact using confocal microscopy and three distinct methods of cluster identification and measurement of receptor clusters in super-resolution datasets: DBSCAN, Pair Correlation and a custom implementation of the Getis spatial statistic. Quantitative analysis of confocal and super-resolution images demonstrated that CTL nanodomains become concentrated in the contact site relative to non-contact membrane after the first hour of exposure and established that this recruitment is sustained out to four hours. DC-SIGN nanodomains in fungal contact sites exhibit a 70% area increase and a 38% decrease in interdomain separation. Contact site CD206 nanodomains possess 90% greater area and 42% lower interdomain separation relative to non-contact regions. Contact site CTL clusters appear as disk-shaped domains of approximately 150-175 nm in diameter. The increase in length scale of CTL nanostructure in contact sites suggests that the smaller nanodomains on resting membranes may merge during fungal nanodomain structure, or that they become packed closely enough to achieve sub-resolution inter-domain edge separations of < 30 nm. This study provides evidence of local receptor spatial rearrangements on the nanoscale that occur in the plasma membrane upon pathogen binding and may direct important signaling interactions required to recognize and respond to the presence of a relatively large pathogen.